Nuevos táxones para la Flora de la Montaña Palentina (España). - Aru, Mª Bárbara; de Paz, Elena; Martínez, Ruth; Alonso, Raquel; García, Marta Eva (Acta Botanica Malacitana, 2008)
New taxa in Palencia’s Mountain flora (Spain) Palabras clave. Corología, taxon, plantas vasculares, Palencia, España. Key words. Chorology, taxa, vascular plants, Palencia, Spain.